Tumor Protein 53-Induced Nuclear Protein 1 Enhances p53 Function and Represses Tumorigenesis - Shahbazi, Jeyran; Lock, Richard; Liu, Tao (Frontiers in Genetics, 2013)
Tumor protein 53-induced nuclear protein 1 (TP53INP1) is a stress-induced p53 target gene whose expression is modulated by transcription factors such as p53, p73 and E2F1. TP53INP1 gene encodes two isoforms of TP53INP1 proteins, TP53INP1α and TP53INP1β, both of which appear to be key elements in p53 function. When associated with homeodomain-interacting protein kinase-2 (HIPK2), TP53INP1 phosphorylates p53 protein at Serine 46, enhances p53 protein stability and its transcriptional activity, leading to transcriptional activation of p53 target genes such as p21, PIG-3 and MDM2, cell growth arrest and apoptosis upon DNA damage stress. The anti-proliferative and pro-apoptotic activities of TP53INP1 indicate that TP53INP1 has an important role in cellular homeostasis and DNA damage response. Deficiency in TP53INP1 expression results in increased tumorigenesis; while TP53INP1 expression is repressed during early stages of cancer by factors such as miR-155. This review aims to summarize the roles of TP53INP1 in blocking tumor progression through p53-dependant and p53-independent pathways, as well as the elements which repress TP53INP1 expression, hence highlighting its potential as a therapeutic target in cancer treatment.